The Ministry of Trade and Industry Decree No. 348 of the Year 2010 As Amended By Decree No. 403 of the Year 2010 = وزارة التجارة والصناعة قرار رقم 348 لسنة 2010 - The Middle East Library for Economic Services (The Middle East Library for Economic Services, 2025)
English & Arabic.